An Efficient Modification at the Hole Transporting Layer/Electrode Interface for High‐Performance Ag‐Electrode‐Based Perovskite Solar Cells. Issue 19 (28th July 2022) - Sun, Jingsong; Zhang, Yongqiang; Wu, Jiarui; Yang, Qing; Yu, Gang; Yang, Xi; Ying, Zhiqin; Sheng, Jiang; He, Haiyan; Shou, Chunhui; Qin, Ganghua; Ye, Jichun
Abstract : Owing to the high power conversion efficiency (PCE) and the solution‐processed fabrication process, perovskite solar cells (PSCs) have attracted wide attention, while most high‐performance PSCs have an n‐i‐p (conventional) configuration that requires the expensive Au electrode. Silver is widely considered as one of the most promising candidates to replace gold as the top electrode material in conventional perovskite solar cells, due to its high conductivity and relatively low price. However, due to the mismatching energy levels between the Ag electrode and the hole transporting layer, Ag electrode‐based PSCs require long‐time aging to achieve their best performance. Herein, an AgI modification layer at the Ag electrode/hole transporting layer interface is employed, which eliminates the s‐shaped bend in current density–voltage ( J – V ) curves of fresh PSCs with the Ag electrode and helps to achieve high‐performance devices without any posttreatment. Optimized devices show a top PCE of up to 20.45% at the beginning, which is higher than that of the fresh (5.80%) and aged (19.31%) pristine counterparts. In addition, the facile method is also available for other iodides such as NH4 I, KI, and CuI. This universal approach enables Ag to be a competitive material for electrode in high‐performance and low‐cost PSCs. Abstract : AgI is introduced between the hole transporting layer and the Ag electrode in perovskite solar cells to increase the work function of the Ag electrode. This approach facilitates the electron collection of the Ag electrode and enables the as‐prepared perovskite solar cells to exhibit a high power conversion efficiency without an aging process.